ANALISA PRODUKSI REFUSE-DERIVED FUEL (RDF) DENGAN METODE BIODRYING DAN MEKANIKAL DARI SAMPAH MENGGUNAKAN SISTEM DINAMIS - Budiyantoro, Wahyu; Hamzah, A. Hadian Pratama; Nurhasanah, . (Ekologia: Jurnal Ilmiah Ilmu Dasar dan Lingkungan Hidup, 2024)
Bandung Regency in 2023 built a TPST (Integrated Waste Management Site) with a capacity of 75 tons/day with the mechanical method "One Day Process" and a capacity of 20 tons/day with the biological method "Biodrying". The fact is that the capacity was not realized according to plan. This study is to evaluate the differences between the Biodrying and One Day One Process methods in producing RDF (Refuse Derived Fuel) and to compile a dynamic model of waste management through sustainable RDF. This study was conducted using a dynamic system using Powersim software with simulations from 2023 to 2024. Existing management was modeled and analyzed with a dynamic system. The results of the study showed that the biodrying method was superior to the capacity and quality of RDF products and had operational cost savings for electricity needs. The modeling results showed that the performance of waste management from 2023 to 2034 was only 10.35 tons/day for the one day one process method and 9.8 tons/day for the biodrying method, as a result, unmanaged waste increased every year. To maximize capacity, the Bandung Regency regional government needs to intervene with policy steps that support the sustainability of TPST.